Effects of Gossypetin on Glucose Homeostasis in Diet-Induced Pre-Diabetic Rats - Karishma Naidoo; Andile Khathi (Molecules, 2024)
Natural flavonoids exert many potential health benefits, including anti-hyperglycaemic effects. However, the effects of gossypetin (GTIN) on glucose homeostasis in pre-diabetes have not yet been investigated. This study examined the effects of GTIN on key markers of glucose homeostasis in a diet-induced pre-diabetic rat model. Pre-diabetes was induced by allowing the animals to feed on a high-fat high-carbohydrate (HFHC) diet supplemented with 15% fructose water for 20 weeks. Following pre-diabetes induction, the pre-diabetic animals were sub-divided into five groups (n = 6), where they were either orally treated with GTIN (15 mg/kg) or metformin (MET) (500 mg/kg), both with and without dietary intervention, over a 12-week period. The results demonstrated that animals in the untreated pre-diabetic (PD) control group exhibited significantly higher fasting and postprandial blood glucose levels, as well as elevated plasma insulin concentrations and increased homeostatic model assessment for insulin resistance (HOMA2-IR) index, relative to the non-pre-diabetic (NPD) group. Similarly, increased caloric intake, body weight and plasma ghrelin levels were observed in the PD control group. Notably, these parameters were significantly reduced in the PD animals receiving GTIN treatment. Additionally, glycogen levels in the liver and skeletal muscle, which were disturbed in the PD control group, showed significant improvement in both GTIN-treated groups. These findings may suggest that GTIN administration, with or without dietary modifications, may offer therapeutic benefits in ameliorating glucose homeostasis disturbances associated with the PD state.